SHROOM3 Deficiency Aggravates Adriamycin-Induced Nephropathy Accompanied by Focal Adhesion Disassembly and Stress Fiber Disorganization - Li-Nan Xu; Ying-Ying Sun; Yan-Feng Tan; Xin-Yue Zhou; Tian-Chao Xiang; Ye Fang; Fei Li; Qian Shen; Hong Xu; Jia Rao (Cells)
SHROOM3 encodes an actin-binding protein involved in kidney development and has been associated with chronic kidney disease through genome-wide association studies. However, its regulatory role in proteinuric kidney diseases and its mechanistic contributions to podocyte homeostasis remain poorly defined. Here, we analyzed single-cell transcriptomic datasets and the Nephroseq database to delineate SHROOM3 expression patterns in proteinuric kidney diseases. Using podocyte-specific SHROOM3 knockout mice and an Adriamycin (ADR)-induced nephropathy mouse model, we demonstrated that glomerular SHROOM3, specifically in podocytes, was upregulated following ADR treatment during the acute injury phase but downregulated in chronic kidney disease. Clinically, the glomerular SHROOM3 expression positively correlated with glomerular filtration rates in focal segmental glomerulosclerosis patients. Genetic ablation of SHROOM3 in podocytes exacerbated ADR-induced proteinuria, diminished podocyte markers (nephrin, podocin, and WT1), and accelerated glomerulosclerosis. In vitro, SHROOM3 deficiency impaired podocyte size and adhesion, concomitant with the downregulation of focal adhesion molecules (talin1, vinculin, and paxillin) and stress fiber regulators (synaptopodin and RhoA), as well as calpain activation and RhoA inactivation. Our findings reveal a critical role for SHROOM3 in maintaining podocyte integrity and suggest its therapeutic potential in mitigating proteinuric kidney disease progression.